Deficits in social behavior and sensorimotor gating in mice lacking phospholipase C beta 1 - Koh, H. -Y.; Kim, D.; Lee, J.; Lee, S.; Shin, H. -S. (BLACKWELL PUBLISHING, 2008)
Abnormal phospholipid metabolism has been implicated in the pathogenesis of schizophrenia, and it was reported that phospholipase C (PLC) beta 1 is reduced in specific brain areas of patients with schizophrenia. However, the causal relationship of the PLC beta 1 gene with behavioral symptoms of schizophrenia remains unclear. To address this issue, we have examined the mutant mice lacking PLC beta 1 for schizophrenia-related phenotypes by performing various behavioral tests, including general locomotor activity, sensorimotor gating, social behaviors, and learning and memory. Phospholipase C beta 1 knockout mice showed hyperactivities in an open field. They showed impaired prepulse inhibition of acoustic startle response, which was ameliorated by a systemic administration of an antipsychotic D2-receptor antagonist, haloperidol. In addition, they showed abnormal social behaviors, such as lack of barbering behavior, socially recessive trait and lack of nesting behavior. Furthermore, they showed impaired performance in the delayed-non-match-to-sample T-maze test. The present results show that the PLC beta 1 mutant mice share some of the behavioral abnormalities that have been reported in patients with schizophrenia. Thus, the PLC beta 1-linked signaling pathways may be involved in the neural system whose function is disrupted in the pathogenesis of schizophrenia.
Keywords: INDUCED DOPAMINE RELEASE; PREPULSE INHIBITION; ANIMAL-MODELS; C ISOZYMES; SCHIZOPHRENIA; AMPHETAMINE; RECEPTORS; ABNORMALITIES; TRANSMISSION; DISORDER